DIMENSIONS OF PERFORMANCE VALUE OF SHARIA MICRO FINANCE INSTITUTION - Ahmad Subagyo (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2022)
ABSTRACTThe performance appraisal of financial institutions is generally measured by using financial ratio indicators. Sharia microfinance institutions are institutions that have been developed by both the Government and the society which have economic and social functions. Social functions that are grown from belief values will have a long-term impacts, both consistency and sustainability. Exploring social values based on Sharia principles is needed to make the operational basis for Islamic microfinance institutions more measurable, both in financial performance and social performance.There are three principles in evaluating the performance of Islamic microfinance institutions, namely (1) the principle of fairness, (2) the principle of honesty, and (3) the principle of partnership. These three principles are the basis for operationalizing LKMS, both in product development, services and corporate governance.Key words: Dimension, Sharia financial principle, Micro finance, fairness, honesty, partnership.